Magkunkuno ti Makina: Python Code for the Computer-Assisted Reading of Hanunuo Mangyan Ambahan - Guillermo, Ramon; University (Archīum Ateneo, 2023)
This essay is primarily a demonstration of a tool written in Python for the computer-assisted reading of the ambahan poetry of the Hanunuo Mangyan ethnolinguistic group on the island of Mindoro. The software tool has been designed as a pedagogical aid for the human reading of ambahan texts as well as a research implement for the analysis of untranscribed and unstudied ambahan. Based on a knowledge of the internal workings of the Surat Mangyan writing system, the tool automatically generates different possible readings of an ambahan text based on an ambahan word list.KEYWORDS: HANUNUO MANGYAN • AMBAHAN • SURAT MANGYAN • BAYBAYIN • COMPUTER-AIDED READING